Management Wound Dehiscance with Heavy Exudate: A Literature Review - Florensia, Lima; Rosaline, Mareta Dea; Anggraeni, Diah Tika; Anggraini, Nourmayansa Vidya; Lestari, Pipit (Jurnal Penelitian Perawat Profesional, 2024)
Wound dehiscenceis a serious postoperative complication that can lead to increased morbidity, extended hospitalization, and higher healthcare costs. This research aims to synthesize the current evidence on the management strategies for deshiscence wounds with heavy exudate. Literature review through several stages is making questions, identification, eligibility, selection of article inclusion, and screening. The Selection Process is listed in the framework of the review literature. Research used PICO, articles published from 2019 to 2024 in English, and searches came from online database are “Pubmed”, “ProQuest”, Science Direct”. Six high-quality articles showed different results adjusted to the system and the conditions of where the research was conducted. The results of the reviewed article focus on wound dehiscence with heavy exudate presents significant challenges in clinical wound management. The optimal approach involves a combination of appropriate exudate management and infection controls. Studies included in this review highlighted the importance of individualized treatment plans for patients with dehiscence and heavy exudate.